Budget transparency and internal revenue mobilisation at sub-national government level: evidence from Nigeria (Public Sector Economics - submission site, 2022)
Internal revenue mobilisation by governments at the sub-national level has been low in Nigeria. In view of the rise in the level of budget transparency at the subnational level in recent times, this study examines the hypothesis that improved budget transparency leads to greater revenue mobilisation. The study adopts both cross-sectional and panel regression analyses based on data for 2015, 2018 and 2020. The findings suggest that the hypothesis that improved budget transparency improves revenue mobilisation cannot be rejected, but population density (urbanisation), poverty and unemployment are the dominant factors that explain revenue mobilisation by the state governments in Nigeria. The study also reiterates the need to control corruption in order to make sustainable progress in revenue mobilisation at sub-national level.